The Effect of Midwifery-Led Care Intervention on Maternal and Neonatal Outcomes in Low-Risk Pregnancies: A Prospective Cohort Study - Dwi Ris Hasanah; Lili Nurmaliza (Yayasan Media Utama Sains, 2025)
Background: Midwifery-led care (MLC) is a continuity of care model that positions midwives as the primary responsible providers in managing low-risk pregnancies. Despite endorsement by the World Health Organization, its implementation in Indonesia remains limited. This study aimed to analyze the effect of MLC intervention on maternal and neonatal outcomes in low-risk pregnancies.Methods: A prospective cohort study was conducted at four primary health centers in Surabaya, Indonesia, from January to December 2024. A total of 240 low-risk pregnant women meeting inclusion criteria were allocated into two groups: MLC intervention (n=120) and conventional care control (n=120). Outcomes measured included preeclampsia, preterm delivery, cesarean section, postpartum hemorrhage, low birth weight, neonatal asphyxia, and maternal satisfaction. Data were analyzed using chi-square test, independent t-test, and multivariate logistic regression with significance set at p<0.05.Results: The MLC group demonstrated significantly better maternal outcomes, including lower cesarean section rate (15.7% vs 28.2%; p=0.018), lower preeclampsia incidence (5.2% vs 13.7%; p=0.024), and lower postpartum hemorrhage (3.5% vs 10.3%; p=0.034). Neonatal outcomes also showed significant differences in low birth weight (4.3% vs 12.0%; p=0.029) and neonatal asphyxia (2.6% vs 8.5%; p=0.041). Overall maternal satisfaction was higher in the MLC group (92.2% vs 71.8%; p<0.001). Multivariate analysis identified MLC as a protective factor against adverse maternal-neonatal outcomes (OR=0.42; 95% CI: 0.24–0.73; p=0.002).Conclusion: Midwifery-led care intervention significantly improves maternal and neonatal outcomes in low-risk pregnancies and enhances maternal satisfaction with care. This model is recommended for broader implementation within the Indonesian maternal and child healthcare system.